Promoting economic recovery: the silver lining of digital transformation and corporate innovation - Du, Zhuo-Ya; Wang, Qian (Technological and Economic Development of Economy, 2025)
With the unstable international environment, the global economy has experienced a slowcession. Previous research on digital innovation in firms has often neglected the impact of macroeconomic cycles. This paper examines the moderating effect of the economic slowcession in the digital transformation and corporate innovation nexus, by using the China’s A-share listed companies’data during 2001 and 2021. The empirical results find that the positive impact of digitization on innovation is countercyclical. During recession, the positive impact of digital transformation on innovation is even greater compared to economic prosperity. Grouped regression results indicate that State-owned listed companies, Non-high tech companies, Large-scale companies, and Eastern companies are more affected by the positive moderating effect of the recession. This indicates that getting out of recession requires more aggressive support of these companies, which promotes innovation and economic recovery. This study provides a useful reference for countries in recession and provides an important complement to traditional economic cycle theory and innovation cycle theory. First published online 15 November 2024